Tactical behavior of high-level male marathon runners - García-Manso, J. M.; Martínez-Patiño, M. J.; de la Paz Arencibia, L.; Valverde-Esteve, T. (Scandinavian Journal of Medicine & Science in Sports, 2021)
This study analyzes the strategy used by the best male runners who participated in one of the major city marathons (Frankfurt Marathon, 2008-2018), the all-time performances <2:04:00, the male world records achieved during the 21st century and the Nike Breaking2 Project and INEOS 1:59 Challenge (total = 235 races). The races of the best runners in the Frankfurt Marathon (top 10) were analyzed (n = 110 runners, range: 2:03:42-2:14:05 hours); the runners were divided into two groups according to the tactical used. The pace of Group A (stable pace) remained steady throughout the race, while in Group B (decrease in running speed toward the end of the race) a moderate, but significant drop in speed was detected (P = .001), starting from halfway through the race and getting sharper from the 30th kilometer (30-35 km = 1.6%, P = .001 - 35-40 km = 4.3%, P = .001 - 40-42.195 km: 3.9%, P = .001, total = ˜10%). In the races in which the world record is achieved, the running speed tends to be steady and relatively conservative during the first stretch of the race, increasing smoothly in the second half and achieving a significant increase in the last 2195 m of the race (P = .016, ES = 1.14). Among all the possible strategies, running at a steady pace throughout the race seems the most effective option, especially when priority is given to time rather than position (ie, world records and best all-time races).